Akulturasi Arsitektur Cina dan Melayu pada Istana Niat Lima Laras Sumatera Utara - Meylani, Ade; Dafrina, Armelia; Saputra, Eri (Rifa'Institute, 2023)
Niat Lima Laras palace is a relic of the Lima Laras Sultanate in North Sumatra. Niat Lima Laras Palace was founded by Datuk Mad yudha, who was the eleventh king of the Lima Laras Kingdom. The palace was built in 1907 until its completion in 1912. Formerly the palace was inhabited by Datuk mad yudha and his family as a residence as well as a center of political, social and economic power for the Lima Laras community. But now the palace is left empty and used as a historical tourist attraction. In the Palace building, there has been architectural acculturation because the construction of the palace involved Chinese groups who had settled in the Lima Laras and the surrounding Lima Laras community as building coolies. This study aims to determine the influence of acculturation of Chinese and Malay architecture applied to the building of Niat Lima Laras Palace. The method used is a descriptive-qualitative method. Analyzing the data descriptively is by analyzing theories related to the architectural characteristics of Niat Lima Laras Palace, then comparing these theories to this Palace, in order to draw conclusions. The results of the analysis showed that the building acculturated Chinese and Malay architecture. The dominant palace applies acculturation of Malay architecture such as stage-shaped palaces, installation of walls, floors, the shape of doors and windows and their colors and ornaments. There is also the application of Chinese architectural acculturation such as the main concept of symmetrical palaces, roof shapes, materials used, colors and ornaments.